UNTANGLING THE KNOTS: NAVIGATING THE COMPLEXITIES OF SHARI’AH COMPLIANCE AND GOVERNANCE IN ISLAMIC FINANCE - Jalalluddin Murad; Muhammad Azim Borahan; Muhammad Irfan Sa’id; Nurhidayah Yahya (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Islamic finance, firmly anchored in the principles of Shari’ah law, presents a financial system designed to operate following religious and ethical standards. The cornerstones of this system are Shari’ah compliance and governance, which play pivotal roles in maintaining its integrity. However, achieving effective Shari’ah compliance and governance within the dynamic and evolving landscape of Islamic banking remains a formidable task. This study explores the multifaceted challenges faced in pursuing Shari’ah compliance and governance in Islamic finance. Scholars’ myriad interpretations of Shari’ah principles, the lack of standardised jurisdiction, and the ever-changing nature of financial products and services pose significant obstacles. Through an extensive exploration of these challenges, this research sheds on the complexities inherent in Islamic finance, providing valuable insights and perspectives. By investigating the mechanisms employed by financial institutions, the roles of Shari’ah scholars and advisory boards, and the development of regulatory frameworks, this study aims to offer practical solutions and best practices that can be implemented to navigate the intricacies of Shari’ah compliance and governance. We hope the hope will serve as a valuable resource for practitioners, scholars, and policymakers, facilitating a more robust and ethically sound Islamic finance industry.